Ministry of Labour and Vocational Training - Irfani Suar; Shandy Tresnawati (Formosa Journal of Multidisciplinary Research, 2023)
The learning process at the time of development of information and communication technology (ICT) such as this allows the teacher absent in class. The learning process is no longer dependent on the teacher as the only learning resources, and can take place anytime and anywhere. The learning process is no longer just a form of verbal communication between teachers and students. With the rapid development of ICT in education and the Internet as an integral part in it, many educational institutions offers web-based learning, or often referred to as online lectures or E-learning. This type of learning such as course requires good and maximum management, so that learning objectives can be achieved. Based on author observations, the interest of Indonesian youth against animation is increase over time. Meanwhile the available of information is still little or difficult to get, while Cimahi Creative Association (CCA) has a forum that can facilitate and accommodates its members to free ask questions and share information about animation between the members. Therefore, after getting to know the function of e-learning applications, finally the author decided to choose a topic about “E-learning Management System in Cimahi Creative Association (CCA)” which aims to facilitate the dissemination of relating information to members wherever they are.